Effect of Weight Passanger to Stopping Distance and Braking Pedal Force of CBR 250 CC - Abduh, Muhammad (2011)
Braking system is becoming one of the important aspects of the vehicle because it is one of the safety systems. Vehicle that traveling at higher speed must fully equipped with more reliable braking system. Reliable braking system is important ro reduce speed or to stop vehicle. Vehicle at high speed make unproportional braking between front and rear wheel, it make one of the wheel locking. Also the rider habbit that usually using only rear brake to reduce speed. It dangerous for the vehicle because it becoming unstable. Combined brake system is more reliable to maintain braking proportion between front and rear wheel. As a braking vehicle decelerates or during the braking process, there is weight transfer, removes weight from the rear wheels and results in a minimum stopping distance. In this research investigates we present an analysis of the minimum stopping distance problem taking into acount the effect of weight transfer on (i) one passeger on vehicle (ii) two passegers on vehicle. On the other, there is weight transfer to the front axle. It makes changing normal load on each wheel. With normal load can calculate how many braking pressure.